Manual Version of 3D Printing - Lytvynenko, Yu.M.; Ostapenko, S.O.; Rogozinsky A.А.; Solonin, Yu.M. (Science and Innovation, 2024)
Introduction. The program of colonization of the Moon and Mars is gradually approaching the practical phase. Researchers are actively discussing various aspects of the presence of people on the surface of the planets. Problem Statement. The number one problem is housing construction: materials and construction technologies. The use of regolith — the lunar or the Martian soil — is supposed to be used as a building material. The construction technology involves the placement of astronauts heating furnace on the lunar surface for sintering bricks, followed by laying them in building structures. The bricks will print on a 3D printer. This idea will require the development and delivery of a 3D printer to the lunar base. Purpose. It is interesting to check the possibilities of simple and cheap options for creating building elements in the conditions of the lunar surface in the absence of a 3D printer and complex heating devices. The purpose of the research is to make a simple product by an additive method, modeling the process of 3D printing without expensive and complicated instruments and devices. Materials and Methods. The manual version of 3D printing using concentrated solar energy from minimally processed local regolith is a simple, economical method of making building components on the surface of the Moon or Mars. The materials used were sand and basalt of terrestrial origin. All necessary operational work for modeling the 3D printing process was done manually. Various devices were used to concentrate the sun's rays on the basis of paraboloid concentrators to create a thermal source of the printer. Results. Simple products from basalt powders and mixtures of basalt with sand were obtained by an additive method without the use of complex expensive equipment. A primitive installation for a 3D process and a heating device from paraboloid concentrators can be easily assembled from structural elements brought from Earth. Conclusions. Manual 3D printing of a minimally processed local regolith using concentrated solar energy is a simple, economical method of making building components on the surface of the Moon or Mars.